Analisa Dampak Kompetisi Politik terhadap Kebijakan Dana Alokasi Umum pada Kabupaten/Kota di Provinsi Papua dan Provinsi Papua Barat - I Kadek Marssel Bagia Sedana (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2026)
Democracy is a slow process of making the right decisions, rather than immediately making the wrong ones. With democracy, every citizen is given the same rights to have an opinion, make decisions, and change their lives for the better. Some previous studies have shown that the amount of funds allocated tends to correlate with the area controlled by the party that controls the government, in this case a political party. This study will focus on examining and understanding the impact of political competition on DAU policy in districts/municipalities in Papua and West Papua provinces. This study uses quantitative analysis of secondary data with research objects in all districts and cities in Papua and West Papua Provinces in the 2014-2024 period. The analytical method used in this study is panel data regression analysis. The results found in this study are a number of variables such as HHI, IKK, Area, and Total Population have a significant correlation and influence on the amount of DAU per capita in a number of districts and cities in Papua and West Papua Provinces. Then, based on the analysis using panel data regression analysis, it is known that political competition, as measured by HHI, has a direct effect on the DAU allocation in a number of districts and cities in Papua and West Papua Provinces.